Biorecognition on Graphene: Physical, Covalent, and Affinity Immobilization Methods Exhibiting Dramatic Differences. Issue 1 (22nd October 2012) - Loo, Adeline Huiling; Bonanni, Alessandra; Pumera, Martin
Abstract The preparation of biorecognition layers on the surface of a sensing platform is a very crucial step for the development of sensitive and selective biosensors. Different protocols have been used thus far for the immobilization of biomolecules onto various electrode surfaces. In this work, we investigate how the protocol followed for the immobilization of a DNA aptamer affects the performance of the fabricated thrombin aptasensor. Specifically, the differences in selectivity and optimum amount of immobilized aptamer of the fabricated aptasensors adopting either physical, covalent, or affinity immobilization were compared. It was discovered that while all three methods of immobilization uniformly show a similar optimum amount of immobilized aptamer, physical, and covalent immobilization methods exhibit higher selectivity than affinity immobilization. Hence, it is believed that our findings are very important in order to optimize and improve the performance of graphene‐based aptasensors.